Faraday's chemical history of a candle - Faraday, Michael, 1791-1867. (Chicago, Ill. : Distributed by Independent Publishers Group, 1988)
Presents a newly illustrated edition of Faraday's six classic lectures that provide an introduction to the principles of combustion. Includes twenty-two experiments that demonstrate the argument of the lectures.
Includes index.
Originally published as: A course of six lectures on the chemical history of a candle. 1861.
7-10.
Young Adult
Keywords: Candles -- Juvenile literature; Chemistry -- Experiments -- Juvenile literature; Combustion -- Juvenile literature; Candles; Chemistry -- Experiments; Combustion; Experiments; Candles; Chemistry